Feminist scholars working around the neoliberal university. Issue 1 (2nd January 2019) - Acker, Sandra; Wagner, Anne
ABSTRACT: A considerable scholarship now describes the increasing neoliberalization of universities and the accompanying impacts on academic research and researchers. However, less attention has been devoted to issues of research project leadership, especially for academics with feminist commitments. This article reports results of a qualitative study of 12 senior academic women from 6 countries who are known for feminist research and explores how they pursue their projects in the context of contemporary changes and challenges. Rather than positioning faculty as passive participants, this study acknowledges their agency within institutional structures, albeit somewhat constrained. The results reveal the range of strategies employed by feminist researchers in various national contexts that enable them to maintain their critical focus despite increasing pressures to conform to neoliberal agendas.